Romanian Energy System Analysis (Production, Consumption, and Distribution) - Michael Fratita; Florin Popescu; Eugen Rusu; Ion V. Ion; Răzvan Mahu (Energies, 2023)
The aim of this paper is to provide a comprehensive overview of how electricity is produced from different sources and the electricity needs of the consumer. According to the Green Deal pact, the objective is to gradually reduce polluting emissions in the energy sector by 2050. In the meantime, the CO2 intensive thermal power plants (those using coal and heavy oil) will be closed and strategic investments in green energy sources will be pursued. This paper presents a detailed analysis of the profile of the Romanian electricity producer over a period of one year. Furthermore, this paper explores the possibility for the energy producer to adapt to consumer demand to reduce electricity imports, strategic locations for the installation of farms using renewable energy, and the current capacity of the national distribution system. This paper analyses electricity only quantitatively and not qualitatively, as well as the way the supplier follows consumers’ need. The paper concludes on possible problems that may arise from the case of green energy.